Effects of triticale cultivars grown in a Mediterranean environment on biomass yield and quality - R. Motzo; F. Boe; G. Pruneddu; F. Giunta; A. Cannas (Italian Journal of Animal Science, 2010)
Triticale is a valuable crop in Mediterranean environments because its growth capacity at low temperatures and its precocity make it possible to obtain high biomass yields in early spring. Precocity of triticale is particularly appreciated in Mediterranean environment, where irrigation allows the sowing of a spring–summer corn crop after a winter cereal crop has been harvested for silage.